2012
DOI: 10.2134/agronj2012.0091
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Performance of Jerusalem Artichoke Clones in a Semiarid Region of China

Abstract: Th is study investigated biomass yield and growth characteristics of 26 Jerusalem artichoke (Helianthus tuberosus L.) clones and assessed it as a bioenergy crop for a semiarid region of the Loess Plateau in China. Genotype, year, and genotype × year interaction contributed to diff erences in crop development, growth characteristics, and biomass yields (dry matter). Generally, biomass yields in 2011 were lower than in 2008, mainly due to a more severe soil moisture defi cit in 2011. Shoot and tuber biomass yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 27 publications
1
29
1
1
Order By: Relevance
“…Several studies were conducted to determine the effects of water stress on tuber yield and biomass of Jerusalem artichoke in both temperate (Conde et al, 1991;Losavio et al, 1997;Schittenhelm, 1999;Monti et al, 2005;Liu et al, 2012) and tropic regions (Ruttanaprasert et al, 2014). However, these previous studies did not focus on determining the effects of soil moisture content on tuber dry weight and total biomass (including root mass) of Jerusalem artichoke with different levels of drought resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were conducted to determine the effects of water stress on tuber yield and biomass of Jerusalem artichoke in both temperate (Conde et al, 1991;Losavio et al, 1997;Schittenhelm, 1999;Monti et al, 2005;Liu et al, 2012) and tropic regions (Ruttanaprasert et al, 2014). However, these previous studies did not focus on determining the effects of soil moisture content on tuber dry weight and total biomass (including root mass) of Jerusalem artichoke with different levels of drought resistance.…”
Section: Discussionmentioning
confidence: 99%
“…tolerant to drought should be the best long-term solution to the problem. Effects of drought stress on tuber dry weight, biomass (Conde et al, 1991;Losavio et al, 1997;Schittenhelm, 1999;Monti et al, 2005;Liu et al, 2012;Ruttanaprasert et al, 2014) harvest index (Conde et al, 1991;Ruttanaprasert et al, 2015) and water use efficiency (Conde et al, 1991;Janket et al, 2013) of Jerusalem artichoke has been reported in several studies. In temperate regions, drought stress reduced Jerusalem artichoke tuber yield by 20% (Conde et al, 1991;Losavio et al, 1997) but increased water use efficiency by 7-35% and harvest index by 21% (Conde et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, hundreds of accessions have been added to the plant germplasm collections worldwide [11]. For example, in the U.S., Jerusalem artichoke collections are maintained at the North Central Regional Plant Introduction Station at Iowa State Substantial genetic variation among 59 Jerusalem artichoke clones collected in China was reported by Liu et al [12], and the biomass yield and the growth characteristics of 26 Jerusalem artichoke clones were assessed for the semiarid region of the Loess Plateau in China [13]. Recently, Puttha et al [14] reported genetic variability for qualitative and quantitative traits among 79 Jerusalem artichoke accessions, and Sennoi et al [15] evaluated 91 Jerusalem artichoke genotypes related to tolerance to diseases and lesions, days to permanent wilting, plant height, and shoot and root dry weight under greenhouse conditions.…”
Section: Genetic Resourcesmentioning
confidence: 99%
“…Jerusalem artichoke, which is particularly suited to dry and poorly-fertile soils, has a greater yield per unit area than potatoes [13,17]. Jerusalem artichoke is moderately salt tolerant based on a rate of decrease in dry tubers and shoot biomass under saline soil conditions in a greenhouse [18].…”
Section: Ecological Adaptability Of Jerusalem Artichokementioning
confidence: 99%